HYDRAULIC SIMULATION OF FLASH FLOOD AS TRIGGERED BY NATURAL DAM BREAK - Yanuar Tri Kurniawan (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2013)
On January 1st, 2006 flash flood disaster (in Indonesia is known as banjir bandang) occurred in Kaliputih River, Jember District of East Java Province. This disaster resulted in more than 80 people were killed and hundreds were injured. The disaster was caused by natural dam break. The natural dam was formed by landslide due to heavy rainfall. After the January 2006 disaster, new cracks and crevices were found in the upstream area of Kaliputih River. Based on this condition, it cannot be disregarded to avoid repetition of similar disaster in the future. Therefore, it is required to conduct mitigation efforts in order to anticipate similar disaster in the future. One of the mitigation efforts is modeling simulation of the past event. The understanding which is obtained from the simulation can be used as reference to arrange other mitigation efforts plan and action .Modeling simulation of the January 2006 flood was conducted by involving 1-D model of HEC-RAS version 4.1.0 software. Flood hydrograph was obtained by analyzing related hydrologic aspects using Nakayasu method. The natural dam model was interpreted from field observation and related references. Some assumptions related to study constraints were taken. Model calibration was conducted by repeating simulation using fixed discharge and parameter values in a certain range. The observations were carried out to the maximum water surface elevation and it was traced to the downstream river.Calibration model result showed that the height of natural dam significantly influence changes of water surface elevation at control point. Tracing of flood result in reconstruction of January 2006 flood showed the conformity with the real event. It was observed from the arrival time of flood at certain location. From obtained results, it can be concluded that simulation modeling gave the acceptable results.